Community Composition and Metabolic Potential of Endophytic Actinobacteria From Coastal Salt Marsh Plants in Jiangsu, China - Chen, Pan; Zhang, Chunmei; Ju, Xiuyun; Xiong, Youwei; Xing, Ke; Qin, Sheng (Frontiers in Microbiology, 2019)
The diversity and functional roles of the plant associated endophytic actinobacteria in unique habitats remain poorly understood. In this paper, we examined the phylogenetic diversity and community composition of endophytic actinobacteria associated with native coastal salt marsh plants in Jiangsu, China using a combination of cultivation and 16S rRNA gene-based high-throughput sequencing (HTS) methods. Further, we evaluated the antifungal, fibrinolytic activities and the secondary metabolite biosynthesis potential of isolates via gene screening. A total of 278 actinobacterial isolates were isolated from 19 plant samples. 16S rRNA gene sequencing revealed that the isolates were highly diverse and belonged to 23 genera within the Actinomycetales order, with Streptomyces, Saccharopolyspora, and Pseudonocardia comprising the most abundant genera. In addition, more than ten of the isolates were novel actinobacterial taxa distributed across eight genera. HTS analyses of seven representative plant root samples revealed that Actinobacteria phylum constituted 0.04%–28.66% of root endophytic bacterial communities. A total of four actinobacterial classes, 14 orders, 35 families, and 63 known genera were detected via HTS, and these communities were found to be dominated by the members of the order Actinomycetales including the genera Streptomyces, Mycobacterium, Arthrobacter, Nocardioides, and Micromonospora. In addition, 30.4% of the representative isolates exhibited antifungal activities, 40.5% of them showed fibrinolytic activities, while 43.0% of the strains harbored secondary metabolite biosynthesis genes. These results demonstrated that coastal salt marsh plants in the Jiangsu Province represented an underexplored new reservoir of endophytic actinobacteria, which contain more diverse and novel taxa than other common habitats. The obtained strains are of potential interest in the discovery of bioactive compounds with potential as biocontrol agents and for fibrinolytic enzyme production in the future.